Sức khỏe và y tế ở vùng dân tộc thiếu số - Cường, Bùi Thế (Nhà xuất bản nông nghiệp, 2016)
Following the development of the country, there have been several health care institutions in the country: health care in the traditional society, health care in the centralized planning economy, and - recently - health care in the socialist oriented market economy. Social public welfare subsidization and free services are still accounting for a majority part of the health care system, which is being gradually socialized with the participation of people. To date, infrastructure and manpower resources of health services within the country have been improved and extended. There has been a great effort of the government, especially in the last 5 years, to give priority to health care services in mountainous and ethnic areas. In 1998, the average numbers of sick-beds, of doctors, and of nurses per 10,000 people in the whole country are 19.3, 3.69, and 6.13 respectively; meanwhile, the respective figures in Northern mountainous regions are 22.0, 3.33, and 8.77, and in Tay Nguyen, 23.8, 4.02, and 6.08. At the national level, communes that have health stations make up 94.7% of the total number of communes. In Northern mountainous regions, the respective figure is 90.2% and in Tay Nguyen, 83.2%. The average health care budget per capita in the whole country, in NMR, and in Tay Nguyen is VND 24,810, VND 28,090, and VND 33,280 respectively. The quantity of health care resources has been listed above. The quality of such resources, however, is very low in comparison with other plain areas, partly represented by poor health stations, lacking of equipment, lacking of medicines, and inexperienced workers. In addition, people's access to modern health services is limited by dispersed distribution of population, weak infrastructure, low quality transportation, low incomes, backward disease treatments, etc... It is clear that, in mountainous areas, health care at hamlet level is more appropriate to the local situation than health care at higher levels. Mobile health care should be considered in the areas with special topography and ethnic characteristics. Private health services and "civilian and military" health care are important, and have been supporting each other effectively in many cases. More attention has been paid to health behavior such as accessing medical centers, combining the advantages of traditional and modern medical treatments, selection of forms and improvement of health knowledge and practice, etc.. The paper discusses in details the health situations of mountainous and ethnic people. It also lists and describes some diseases, illness situations, and disease prevention and treatment for children, women, and elderly people, especially in children's health, reproductive health, and family planning. Despite the fact that vaccination has been increased, infant mortality rates in those areas are still rather high (this rate in mountainous areas was more than 50%o while that of the whole country was 36%o in 1996). The rate of women doing prenatal check-ups in the areas is also lower than that of Kinh and Hoa women (44.6% compared with 75.6%). Ethnic women often give birth at home (78.9% compared with 39.4%) for many reasons. Only approximately 9% of ethnic women deliver in State hospitals, and about 12% do it in commune clinics. The average 346 number of children that each woman has in Tay Nguyen in 1999 was 4.68 (children); more than 50% of the women do not use any birth control method in their reproduction age. Some diseases, such as malaria, petechial fever, diarrhoea, etc., though they haven't become pandemic in recent years, are still common in ethnic and mountainous areas. Nutrition, sanitation, and prophylaxis are still at a very low level; HIV/AIDS has appeared in some mountainous areas, especially in border provinces and some provinces with large tourist attractions. Issues of health care and health services in mountainous areas that need to be further discussed are: identifying health service demand of mountainous people; applying appropriate health education; encouraging health care at the hamlet level; implementing policies for managing, organizing, and favoring workers and people in mountainous areas; health care in the new socio-economic situation; disseminating and broadcasting of health services; updating health information, etc.